Ethics in the Supply Chain: Improving Sustainability in Food and Clothing Retail Supply Chains - Ugboma, Patrick (2013)
The purpose of this dissertation is to identify issues ethical issues food and clothing retailers face in their supply chain and identify appropriate tools for tackling such issues. Before recommending such tools, four sub questions were asked and answered using a secondary analysis of data which had been put together by previous researchers. The questioned aimed at answering whether the objectives of a company interfered with its capability to be ethical, whether the length and nature of the supply chain plays a part in its ethical, what each party’s role is in the supply chain and finally, which party is to blame for ethical issues in the supply chain. Upon answering these questions and reviewing the literature, the social audit is considered the best tool for improving sustainability in supply chains though it has its flaws. This leaves room for more improvement to this tool as well as provides researchers with the opportunity to discover new tools which may further improve sustainability in the supply chain.